Analysis the Effect of Landslide Hazard on Land Value Zone in Boyolali Regency - Nurfauzi, Irfan; WIjaya, Arwan Putra; Wahyudin, Yaser (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2023)
Landslides are disasters that often occur in mountainous areas. According to Regional Disaster Management Agency Boyolali Regency from 2019-2021 there were recorded 25 landslides in Selo District. As a result, it has an impact on the loss of both lives and the economy. Indirectly impact on land prices in the area. Therefore, it is necessary to analyze the land values changes??in Selo District in landslide hazard areas. In this study, the land value is obtained based on a land price survey. The results are the land value of Selo District in 2022 can be divided into 113 zones with the highest price of IDR 1,150,240 in zone 1787 and the lowest price of IDR 37,013 in zone 1777. The land value at low landslide hazard has an average of IDR 709,970, the land value at medium landslide hazard has an average of IDR 317,089 and the land value at high landslide hazard has an average of IDR 111,160. By using linear regression obtained the correlation r=-0.880. Shows that if the landslide hazard increases, land prices will decrease. Keywords: Land Value Zone, Landslide Hazard, Land Value changes, Linear Regression, Selo District